2011
DOI: 10.1016/j.febslet.2011.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterisation of human SGLT‐5 as a novel kidney‐specific sodium‐dependent sugar transporter

Abstract: a b s t r a c tSodium glucose cotransporters (SGLT) actively catalyse carbohydrate transport across cellular membranes. Six of the 12 known SGLT family members have the capacity to bind and/or transport monosaccharides (SGLT-1 to 6); of these, all but SGLT-5 have been characterised. Here we demonstrate that human SGLT-5 is exclusively expressed in the kidney. Four splice variants were detected and the most abundant SGLT-5-mRNA was functionally characterised. SGLT-5 mediates sodium-dependent [ 14 C]-a-methyl-D-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
66
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 24 publications
6
66
0
Order By: Relevance
“…In additional analyses, we found that SGLT5, which represents the closest homolog to SGLT4 in kidney, exhibits considerably shorter C-terminus as well as lacks predicted PBD (not shown) despite its Pz sensitivity (K i 1.3 mM and 2.7 mM in the presence of mannose and fructose, respectively [41]). Perhaps, this inhibition is caused by a non-specific interaction involving other region(s) than C-terminus.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In additional analyses, we found that SGLT5, which represents the closest homolog to SGLT4 in kidney, exhibits considerably shorter C-terminus as well as lacks predicted PBD (not shown) despite its Pz sensitivity (K i 1.3 mM and 2.7 mM in the presence of mannose and fructose, respectively [41]). Perhaps, this inhibition is caused by a non-specific interaction involving other region(s) than C-terminus.…”
Section: Discussionmentioning
confidence: 95%
“…This assumption can be supported by the fact that SGLT5 transport is weakly inhibited by high affinity Pz analogs of SGLT2 inhibitors. For example, canagliflozine and dapagliflozine weakly inhibit SGLT5 (IC 50~1 500 nM and 740 nM, respectively) than their strong inhibitory effects in SGLT2 (K i~2 .7 nM and 1.2 nM, respectively) [41].…”
Section: Discussionmentioning
confidence: 99%
“…According to the Human Protein Atlas 18 , SLC5A10 transcript is exclusively found in human kidney cortex. The protein is a Na + -dependent transporter of mannose, fructose, galactose and glucose, responsible for their reabsorption from urine in the brush border of renal proximal tubule cells 19, 20 . Because of its exclusive expression in kidney, genetic variation in this gene is likely related to 1,5-AG concentrations either because it also transports 1,5-AG or because it influences the amount of urinary glucose that competes with 1,5-AG for renal reuptake through SLC5A9 .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings that Adult – FRU rats had renal alterations such as accumulation of fat cells, increases in kidney weight, glomerular sclerosis and inflammatory infiltrates, along with elevated blood-glucose levels, reinforce the idea that glycosylation of proteins, the increased release of proinflammatory cytokines, oxidative stress, and the accumulation of lipid peroxidation products may be the cause of kidney damage [58,60]. Regarding the accumulation of fat cells in the kidneys on the groups that consumed the FRU diet, still is not fully understood the exact mechanism by which the FRU diet induced it, but we believe that some renal glucose transporters, such as GLUT2, GLUT5, NaGLT1, SGLT4 [61,62] and the recently reported SGLT5, which is exclusively expressed in the kidney and transports fructose and mannose [63], may be involved [64]. …”
Section: Discussionmentioning
confidence: 99%